Rumi in a Posthumanist Key: Poetic Ecologies and Ethical Entanglements - Fitrilya Anjarsari (Mahad Aly Al Fithrah, 2026)
Amidst ecological degradation and the acceleration of technoscience, post-humanist ethics are increasingly seeking a vocabulary of responsibility that transcends human exceptionalism. However, existing scholarship rarely brings together Sufi metaphysics and post-humanist theory in a sustained manner, and studies of Rūmī often treat the agency of animals, materials, and supernatural entities merely as metaphors. Through the poetic framework of Jalāl al-Dīn Rūmī, this article bridges this gap by reading selected ghazals and passages from the Masnavī alongside Rosi Braidotti’s relational subject, Karen Barad’s agential realism, and Donna Haraway’s figures of companionship. This article develops a “poetic ecology” as an interpretative method that highlights attention, resonance, and adab as practices of being-with animals, materials, technologies, and invisible beings. Methodologically, this article combines close reading, intertextual interpretation, and conceptual translation, treating images of wind, flutes, moths, and light as sites where agency is distributed and responsibility is felt. Key findings suggest that dhikr and samāʿ function as an ethics of entanglement that disciplines perception, loosens the boundaries between self and world, and shifts responsibility from command towards “response-ability”. This framework explains how devotion can operate as an ethics of entanglement, rather than as a human-centred moral command. Brief vignettes on urban pollution, data infrastructure, and AI in the classroom demonstrate how Rūmī’s imagination can guide ecological care, reparative listening, and humane design. This article reinterprets the khalīfah as a companion species and formulates practical adab for institutional, pedagogical, and technological contexts.